Envelhecimento e intervenções baseadas em mindfulness : efeitos sobre a cognição, estresse e BDNF - Rocha, Bruna Fernandes da (2020)
Introduction: There are factors that can contribute to a healthy aging and have a preventive effect on age related impairments. Mindfulness (mindful attention) got popular because of its benefits in well-being and reduction in anxiety, depression, and stress symptoms. However, research has also demonstrated its relation to cognitive improvements and preventive effects on age related cognitive and functional declines. Furthermore, mindful attention is weakly related to the self-compassion construct, a strong predictor of psychological health. This master's dissertation consists of two studies. The first study is characterized as a systematic literature review. It aimed to verify the therapeutic applicability of mindfulness-based interventions for the elderly population. 28 studies were included for the review. The potential of mindfulness-based programs as a therapeutic tool for elderly is highlighted. Mostly, related to decreasing emotional suffering and increasing well-being. However, there are still few researches about mindfulness aimed specifically for older adults. The second study aimed to investigate the effects of an intervention based on mindfulness and self-compassion on cognitive functioning, levels of mindfulness, stress and BDNF in elderly women. This is an exploratory, quantitative, and longitudinal study, with 43 older aged women assigned to the intervention or the control group. Instruments: Socialdemographic questionnarie; Perceived Stress Scale; Freiburg's Mindfulness Inventory; Lipp's Stress Symptom Inventory for Adults; Mini Mental State Examination; Stroop Attention Test, Logical Memory Test I and II and WAIS-III Digits Subtest; Trail Making Test; Phonemic and Semantic Verbal Fluency Test. The intervention reduced stress symptoms, improved cognitive functions, and improved the levels of mindful attention. Mindfulness and self-compassion based interventions have shown benefits to the elderly population and present protective effects against age related declines. It is highlighted the importance of studies that contribute with preventive measures and the development of a successful aging.